Penerapan Metode Pembelajaran Poject Based Learning Market Day Dalam Mengembangkan Keterampilan Berpikir Kritis - Annisak Irma Lafifah Lafifah; Denok Dwi Anggraini (Jurnal Kajian Anak)
This research aims to investigate the implementation of project-based learning methods in developing critical thinking skills in Group A children at TK Aisyiyah Bustanul Athfal IV Laden Pamekasan. The method used is descriptive qualitative research. The population and sample in this study are Group A students, teachers, and parents directly involved in project-based learning activities. The data collection procedures used in this qualitative research include interviews and observations. The data analysis techniques employed include (1) data reduction, (2) data presentation, (3) conclusion drawing, and verification. The results of this study on the implementation of project-based learning methods at TK Aisyiyah Bustanul Athfal IV Laden Pamekasan indicate that this method is effective in developing children’s critical thinking skills through project-based learning activities such as Market Day, which involves independent and collaborative planning, exploration, and problem-solving. The role of teachers and parents as facilitators greatly supports this learning process.